Argonaute identity defines the length of mature mammalian micrornas - Juvvuna Prasanna Kumar (2013)
Regulation of eukaryotic gene expression by microRNAs, 19-25 nt long non-coding RNAs, plays a major part in organismal development and function. Individual miRNAs often exist as populations of length variants but the mechanisms underlying this heterogeneity are poorly understood. Here we identified a large set of miRNAs that are significantly shortened during mouse nervous system development. This phenomenon, which we refer to as miRNA trimming, occurs at the 3’ end of mature miRNAs following the Dicer processing step. Of the four miRNA-interacting Argonaute paralogs encoded in mammalian genomes, Ago2-bound miRNAs are trimmed with the highest efficiency. This is consistent with the high expression of Ago1 in embryonic brain and an increase in the relative abundance of Ago2 at the later developmental stages. We further show that the trimming efficiency is defined by the structure of the Argonaute PAZ domain interacting with the miRNA 3’ end as well as the identity of the 3’-terminal nucleotide. These results uncover the previously unknown Argonaute role in developmentally regulated changes in the composition of miRNA isoforms.